2008
DOI: 10.1093/molbev/msn232
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Protein-Coding Sequence Evolution with Probabilistic Codon Substitution Models

Abstract: This review is motivated by the true explosion in the number of recent studies both developing and ameliorating probabilistic models of codon evolution. Traditionally parametric, the first codon models focused on estimating the effects of selective pressure on the protein via an explicit parameter in the maximum likelihood framework. Likelihood ratio tests of nested codon models armed the biologists with powerful tools, which provided unambiguous evidence for positive selection in real data. This, in turn, tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
129
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(129 citation statements)
references
References 183 publications
0
129
0
Order By: Relevance
“…Although current site prediction methods arguably represent the most rigorous tools for analyzing selection in DNA sequences (2), it has been suggested that the statistical methods that underpin them have some limitations (40). Specifically, many of these methods require considerable sequence divergence (1) and have difficulty in identifying rare mutational events that are adaptive (40).…”
Section: Discussionmentioning
confidence: 99%
“…Although current site prediction methods arguably represent the most rigorous tools for analyzing selection in DNA sequences (2), it has been suggested that the statistical methods that underpin them have some limitations (40). Specifically, many of these methods require considerable sequence divergence (1) and have difficulty in identifying rare mutational events that are adaptive (40).…”
Section: Discussionmentioning
confidence: 99%
“…We estimated the per-site diversity level as the proportion of non-HXB2 amino acids, assuming that each amino acid residue is independent. Although this is probably an overestimate of the amount of diversity, it is sufficient for the purposes of our analysis in the absence of a phylogeny (4,13). For each DRM site, we ranked the diversity level against all other codons and assessed a median mutation rank for all DRM sites combined.…”
Section: Methodsmentioning
confidence: 99%
“…The selective pressure operating on the core eudicot PDATs was estimated using the ratio (v) of the nonsynonymous substitution rate versus the K S as an indicator (Yang and Bielawski, 2000;Anisimova and Kosiol, 2009): 0 , v , 1 corresponds to purifying selection, v = 1 indicates neutral selection, and v . 1 suggests positive selection.…”
Section: Gene Expansion Pattern and Selective Pressure Analysismentioning
confidence: 99%